Homiletical possibilities and challenges in Colossians. (November 2019) - Sigmon, Casey Thornburgh
Colossians shines a light onto how some early churches on the margins of society adjusted to everyday life in the midst of a non-Christian society. Engaging baptismal liturgy and hymnody, the Colossian authors instruct Christians in the Lycus Valley (western Turkey) to beware of philosophies and ascetic practices competing for their devotion. According to Colossians, the baptized are now living a new life in Christ, the head of the Church and cosmos. New fruit is visible evidence to the outside world of the cosmic reconciliation that occurred through the cross of Jesus Christ. As dramatic as the shift in cosmic order may seem in the first chapters of the letter, however, the latter half creates a challenge for the preacher. The authors seem to accommodate the radical new life in Christ to the wider Greco-Roman culture, resulting in a diminished role for women in the church and an acceptance of the slave–master dichotomy. Both accommodations in Colossians haunt our legacy as Christ's Body in the world today.